ANALISIS KONSEP MANTUNU DALAM UPACARA RAMBU SOLO’ SEBAGAI PEMBENTUK ETOS KERJA ANAK USIA DINI DI KECAMATAN SESEAN, TORAJA UTARA - Yanni Paembonan; Sarce Lu’pi; Ema Ema (SEKOLAH TINGGI TEOLOGI KIBAID, 2023)
Abstract. This aims to analyze concept of mantunu in the Rambu Solo’ as a shaper of early childhood work ethic in Sesean, North Toraja. The method used is qualitative to complete the information according to the problem being studied. Parents say that: when parents die